EFFECT OF TEMPERATURE ON KINETICS AND SORPTION BEHAVIOUR OF TERBIUM (III) IONS ONTO 1-(2-PYRIDYLAZO)-2-NAPHTHOL LOADED POLYURETHANE FOAM - Saeed, M. M.; Ahmed, M. (The Nucleus, 2020)
The sorption behaviour of 9.8 × 10−6 mol l−1 solution of Tb(III) metal ions onto 7.25 g l−1 of 1-(2-pyridylazo)-2-naphthol (PAN) loaded polyurethane foam (PUF) at different temperatures has been investigated. The maximum equilibration time of sorption was found to be 30 minutes from pH 7.5 buffer solution at all temperatures. Different kinetic parameters of adsorption process have been determined. The diffusional activation energy (ΔEads) and activation entropy (ΔS*) of the sorption of Tb(III) ions were found to be 32.2 ± 4.2 kJ mol−1 and 86.2 ± 10.3 J mol−1 K−1, respectively. The thermodynamic parameters such as enthalpy (ΔH), entropy (ΔS) and Gibbs free energy (ΔG) were calculated and interpreted. The positive values of ΔH and ΔS indicate that sorption is endothermic and entropy driven. The adsorption isotherms such as Freundlich, Langmuir and Dubinin – Radushkevich were tested experimentally at different temperatures. The changes in adsorption isotherms constants at different temperatures have been discussed. The differential enthalpy of adsorption (ΔHdiff), entropy of adsorption (ΔSdiff) and free energy of adsorption (ΔGdiff) were determined and found to be 54 ± 3 kJ mol-1, 303 ± 4 J mol-1 K-1 and -40.9 ± 1.7 k J mol-1, respectively. The stability of sorbed complex and possible mechanism involved in adsorption process has been discussed using different thermodynamic parameters and adsorption isotherms.